Analisis Penggunaan Metode Tikrar Pada Program Intensif Menghafal Al-Quran Siswa Di MTs Madinatussalam Tembung - Sahib, M. Azmar Ravi; Junaidi, Junaidi (Yayasan Rahmat Islamiyah, 2024)
The aim of this research is to determine the analysis of the use of the Tikrar method in an intensive Al-Quran memorization program for students at Madinatussalam schools; design, evaluation and analysis. Data was through collected, observation and interviews tests. This study uses a method qualitative. The this results of research that conclude before analyzing the method Tikrar, teacher first the a plan makes. Lessons conducted like teachers in schools other. the Unfortunately, implementation of the analysis the of use of Tikrar method in the intensive Al-Quran memorization program for Madinatussalam students did not go according to plan. Analysis of the use of the tikrar method through an intensive Al-Qur'an memorization program for Madinatussalam students is carried out in several ways, namely at home and memorizing in front of the ustadzah. Evaluation is used after the students present their performance to the tahfidz teacher.